Development of ELISA technique for detecting Clostridium novyi alpha toxin - Lily Natalia (Indonesian Center for Animal Research and Development (ICARD), 1997)
the investigation of infectious necrotic hepatitis . Modification of the indirect ELISA technique in the system used is an inhibition ELISA for antigen . The test samples were liver fluid from dead animals suspected from infectious necrotic hepatitis. To analyse for alpha toxin, microtiter plates were coated with antigen or alpha toxin . The liver fluid sample thought to contain antigen or toxin was then mixed together with reference antiserum containing specific alpha antitoxin of Cl. novyi. Enzyme labelled antiglobulin was then added, followed by enzyme substrate . The difference in colour change between a reference sample containing no antigen or toxin and the test sample solution indicates the amount of antigen or toxin in the test samples . This is a competitive assay; high toxin concentrations result in less colour at the end of the test . The sandwich ELISA technique was sensitive enough to detect as little as 390 ng/ml toxin in liver fluid sample. These results indicate that the ELISA technique is useful for detecting alpha toxin of Cl. novyi and for diagnosing infectious necrotic hepatitis . Keywords: ELISA technique, Clostridium novyi alpha toxin, infectious necrotic hepatitis